2013
DOI: 10.5194/acp-13-4057-2013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ACCMIP outgoing longwave radiation from tropospheric ozone using TES satellite observations

Abstract: Abstract. We use simultaneous observations of tropospheric ozone and outgoing longwave radiation (OLR) sensitivity to tropospheric ozone from the Tropospheric Emission Spectrometer (TES) to evaluate model tropospheric ozone and its effect on OLR simulated by a suite of chemistry-climate models that participated in the Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP). The ensemble mean of ACCMIP models show a persistent but modest tropospheric ozone low bias (5–20 ppb) in the Southern He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 84 publications
4
70
0
Order By: Relevance
“…Bowman et al (2013) suggested that overestimation of the outgoing longwave radiation in the tropical seas of the east Atlantic Ocean and over southern Africa is associated with model ozone errors, a persistent feature in all ACCMIP models, which was also found in this study using the reanalysis. Validation of short-lived species is also important for evaluating the radiative forcing because simulated OH fields influence simulated climates through, for instance, their influences on methane .…”
Section: Implications Into Model Improvements and Climate Studiessupporting
confidence: 64%
See 2 more Smart Citations
“…Bowman et al (2013) suggested that overestimation of the outgoing longwave radiation in the tropical seas of the east Atlantic Ocean and over southern Africa is associated with model ozone errors, a persistent feature in all ACCMIP models, which was also found in this study using the reanalysis. Validation of short-lived species is also important for evaluating the radiative forcing because simulated OH fields influence simulated climates through, for instance, their influences on methane .…”
Section: Implications Into Model Improvements and Climate Studiessupporting
confidence: 64%
“…A complete description of the models along with the experiment design can be found in Lamarque et al (2013). Both the ACCMIP models and chemical reanalysis are interpolated to a 2 • × 2.5 • spatial resolution and 67 levels, following Bowman et al (2013), and then compared with each other. Spatial correlations are computed with consideration of weighting for the latitude.…”
Section: Accmip Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Bowman et al (2013) to avoid different results due to different tropopause definitions [ Stevenson et al, 2004], we define a chemical tropopause as the 150 ppb ozone isopleth, also used by Young et al, (2013) and Rap et al, (2015). Therefore, Z TP in Eq.…”
Section: Long Wave Radiative Effect (Lwre)mentioning
confidence: 99%
“…For example, Bowman et al (2013) used TES retrieved O 3 and IRKs to reduce the inter-model uncertainty of the preindustrial-to-present O 3 RF of the chemistry-climate models participating in the Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP) by 30%. Their study also suggested that the vertical TOA flux sensitivity to tropospheric O 3 is highly variable but is structurally consistent with atmospheric opacity, which determines on the amount of upwelling longwave radiation available for O 3 absorption (Lacis and …”
Section: Introductionmentioning
confidence: 99%